Survey of hepatitis B knowledge and stigma among chronically infected patients and uninfected persons in Beijing, China. (12th June 2016) - Huang, Jiaxin; Guan, Mary L.; Balch, Jeremy; Wu, Elizabeth; Rao, Huiying; Lin, Andy; Wei, Lai; Lok, Anna S.
Abstract: Background & Aims: Hepatitis B virus (HBV) infection carries substantial stigma in China. We surveyed HBV knowledge and stigma among chronic hepatitis B (CHB) patients and persons without HBV infection in Beijing, China. Methods: Four hundred and thirty five CHB patients and 801 controls at Peking University People's Hospital were surveyed. Results: Chronic hepatitis B patients were older (mean 46 vs. 39 years) and more often men (71 vs. 48%) than controls. Mean knowledge score was 11.9/15 for CHB and 9.3/15 for control patients ( P < 0.001). Average stigma score was 22.1/39 for CHB and 19.2/30 for control patients. Controls expressed discomfort with close contact (45%) or sharing meals with CHB patients (39%) and believed CHB patients should not be allowed to work in restaurants (58%) or childcare (44%). Chronic hepatitis B patients felt that they were undesirable as spouses (33 vs. 17%) and brought trouble to their families (58 vs. 34%) more often than controls. Despite legal prohibitions, 40% of CHB patients were required to undergo pre‐employment HBV testing, and 29% of these individuals thought that they lost job opportunities because of their disease status. 16% of CHB patients regretted disclosing their HBV status and disclosure was inversely associated with stigma. Higher stigma was associated with older age, lower education and lower knowledge score among controls; and with lower education, younger age, having undergone pre‐employment HBV testing and regret disclosing their HBV status among CHB patients. Conclusion: Despite high prevalence of CHB in China, our study shows knowledge is limited and there is significant societal and internalized stigma associated with HBV infection. Abstract : See Editorial on Page1582